(untitled) (Canadian Journal of Native Studies, 2026)
Abstract This paper is a comparative exploration of approaches to tender bidding and surety bond use in three Canadian jurisdictions: the Province of Quebec, as Canada’s sole civil law jurisdiction; the common-law jurisdiction of the north-easterly neighboring Province of Newfoundland and Labrador; and, to the north of Quebec, Canada’s newest territorial government, Nunavut. The review will also include an examination of the Indigenous self-governing regions of northern Quebec, Nunavik and northern Newfoundland and Labrador, Nunatsiavut. The research commences with a literature review and discussion of the early history of contract law and the principle of good faith, as well as a review of the historical timeline and evolution of the use of suretyship via surety and other forms of bonds. From the completion of the historical review of tender bidding and surety bonds, the focus of the paper shifts to examining their use within public procurement policies with respect to contracts at the federal level, along with the select provincial, territorial and Indigenous governments. This paper also examines the respective self-government agreements and “land claim agreements,” to ascertain the tendering flexibility and surety bond requirements. This project’s research methodology uses secondary data such as legal studies and case commentaries, as well as relevant political science and sociological papers, along with credible news articles and government webpages. This paper’s research also includes communication with the administrations of the National Aboriginal Capital Corporations’ Association (NACCA), the Territorial Government of Nunavut, the Nunavik regional government and the government of Nunatsiavut.